Asymmetric pallidal neuronal activity in patients with cervical dystonia - Moll, Christian KE; Galindo-Leon, Edgar; Sharott, Andrew; Gulberti, Alessandro; Buhmann, Carsten; Koeppen, Johannes A.; Biermann, Maxine; Bäumer, Tobias; Zittel, Simone; Westphal, Manfred; Gerloff, Christian; Hamel, Wolfgang; et al. (Frontiers in Systems Neuroscience, 2014)
The origin of asymmetric clinical manifestation of symptoms in patients suffering from cervical dystonia (CD) is hitherto poorly understood. Dysregulated neuronal activity in the basal ganglia has been suggested to have a role in the pathophysiology of CD. Here, we re-assessed the question to what extent relative changes occur in the direct versus indirect basal ganglia pathway in CD, whether these circuit changes are lateralized, and how these alterations relate to CD symptoms. To this end, we recorded ongoing single cell and local field potential (LFP) activity from the external (GPe) and internal pallidal segment (GPi) of thirteen CD patients undergoing microelectrode-guided stereotactic surgery for deep brain stimulation in the GPi. We compared pallidal recordings from CD patients operated under local anaesthesia (LA) with those obtained in CD patients operated under general anaesthesia (GA). In awake patients, mean GPe discharge rate (52 Hz) was lower than that of GPi (72 Hz). Mean GPi discharge ipsilateral to the side of head turning was higher than contralateral and correlated with torticollis symptom severity. Lateralized differences were absent at the level of the GPe and in recordings from patients operated under GA. Furthermore, in the GPi of CD patients there was a subpopulation of theta-oscillatory cells with unique bursting characteristics. Power and coherence of GPe- and GPi-LFPs were dominated by a theta peak and also exhibited band-specific interhemispheric differences. Strong cross-frequency coupling of low-gamma amplitude to theta phase was a feature of pallidal LFPs recorded under LA, but not GA. These results indicate that CD is associated with an asymmetric pallidal outflow. Based on the finding of symmetric neuronal discharges in the GPe, we propose that an imbalanced interhemispheric direct pathway gain may be involved in CD pathophysiology.